2023
DOI: 10.1002/asjc.3231
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neural network control of multiple‐sectioned flexible riser with time‐varying output constraint and input nonlinearity

Fengjiao Liu,
Xiangqian Yao,
Yu Liu

Abstract: In this paper, an adaptive neural network controller is proposed for vibration suppression of a multisectional riser system with unknown boundary disturbance, time‐varying asymmetric output constraint, and input nonlinearity. The considered riser system is composed of a continuous connection of several different pipes, and its dynamic models are represented by a set of multiple continuously connected partial differential equations (PDEs) and an ordinary differential equation (ODE) at the top boundary. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Additionally, the controller design is based on RBFNN and LKFs in order to handle the time delays in the system. A large number of research results [57][58][59][60] have confirmed the excellent ability of RBFNN to approximate the unknown term, so our proposed control scheme can also deal with the parameter uncertainty of the vehicle system, including vehicle mass, rotational inertia, and tire stiffness.…”
Section: Introductionmentioning
confidence: 69%
“…Additionally, the controller design is based on RBFNN and LKFs in order to handle the time delays in the system. A large number of research results [57][58][59][60] have confirmed the excellent ability of RBFNN to approximate the unknown term, so our proposed control scheme can also deal with the parameter uncertainty of the vehicle system, including vehicle mass, rotational inertia, and tire stiffness.…”
Section: Introductionmentioning
confidence: 69%